Multinational firms and the currency crisis - Max Iklé (Intereconomics, 1971)
Every currency crisis of recent years has been accompanied by a migration of billions of short-term money. Both experts and laymen have again and again been amazed at the speed at which, at relatively short notice, these enormous sums could be mobilised.
Keywords: 330; International Monetary Policy